Pengendalian Risiko dalam Akad Pembiayaan Murabahah dan Mudharabah pada Bank Pembiayaan Rakyat Syariah (BPRS) Madina Yogyakarta - Miqdad Miqdad; Abdul Wahab Muhaimin; Dawud Arif Khan (Lembaga Pengembangan Kinerja Dosen, 2025)
Risk control mechanisms in murabahah and mudharabah financing are implemented to anticipate potential risks arising from the customer's position. The objective is to uphold sharia principles while ensuring that the mitigation efforts by Sharia Rural Financing Banks (BPRS) provide advantages for both the bank and the wider community, particularly the customers. This qualitative case study investigates BPRS Madina in Yogyakarta. The findings reveal that BPRS Madina adopts several approaches to mitigate risks in murabahah and mudharabah financing. First, it verifies the completeness of financing documents using available data sources. Second, it checks for any history of problematic financing by the customer. Third, when necessary, the bank conducts restructuring to minimize risk. Additionally, BPRS Madina carries out risk control measures based on DSN MUI Fatwa No. 04/DSN-MUI/IV/2000 on Murabahah Financing and No. 07/DSN-MUI/IV/2000 on Mudharabah. While Islamic financial institutions do not inherently require guarantees in financing, they are permitted to request collateral to prevent losses. This collateral is not intended to ensure full compliance with the contract terms but rather to safeguard the return of the capital provided. Lastly, the risk management strategies employed by BPRS Madina for murabahah and mudharabah financing are deemed effective, as less than 1% of customers currently encounter issues, and operational risks remain well-managed.